2005
DOI: 10.1161/01.str.0000185798.78817.f3
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcomes in Patients Who Do Not Receive Intravenous Tissue Plasminogen Activator Because of Mild or Improving Ischemic Stroke

Abstract: Background and Purpose-Some patients with mild or improving ischemic stroke symptoms do not receive intravenous tissue plasminogen activator (tPA) because they look "too good to treat" (TGT); however, some have poor outcomes. Methods-We retrospectively analyzed data from a prospective single-center study between 2002 and 2004. TGT patients were those arriving within 3 hours of symptom onset and not treated with intravenous tPA solely because of mild or improving symptoms. Results-Of 128 patients presenting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
3
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(178 citation statements)
references
References 10 publications
3
164
3
8
Order By: Relevance
“…This seems to be of special interest given the contradicting significance attributed to brief cerebral ischemia. Whereas some studies found that transient cerebral ischemia may improve stroke outcome by serving as a preconditioning stimulus that triggers neuroprotective pathways in the brain (Castillo et al, 2003;Wegener et al, 2004), others demonstrated secondary deterioration on MRI (Fujioka et al, 1999a) or neurological function (Johnston et al, 2003;Smith et al, 2005) similar to the herein observed pathology. Hence, withholding treatment in these patients should be reconsidered and more aggressive interventions may be indicated in patients with rapidly improving symptoms, who currently are often treated with little urgency or concern (Johnston et al, 2003;Smith et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…This seems to be of special interest given the contradicting significance attributed to brief cerebral ischemia. Whereas some studies found that transient cerebral ischemia may improve stroke outcome by serving as a preconditioning stimulus that triggers neuroprotective pathways in the brain (Castillo et al, 2003;Wegener et al, 2004), others demonstrated secondary deterioration on MRI (Fujioka et al, 1999a) or neurological function (Johnston et al, 2003;Smith et al, 2005) similar to the herein observed pathology. Hence, withholding treatment in these patients should be reconsidered and more aggressive interventions may be indicated in patients with rapidly improving symptoms, who currently are often treated with little urgency or concern (Johnston et al, 2003;Smith et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…[5][6][7][8] We found that about one-quarter of the patients who did not receive thrombolysis were noted to have neurological deficits that were too mild for treatment, which is similar to data from a 2001 study by Barber and colleagues. 18 However, about one-third of these patients will have an outcome of death or disability, 18,19 which suggests that some of these patients could have undergone treatment.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Prior studies have found that this is the most common reason given for not treating otherwise eligible patients with IV tPA, yet multiple cohorts have found that up to one-third of patients with mild stroke symptoms at presentation will have poor long-term outcomes. [34][35][36][37] Patients with mild stroke symptoms were largely excluded from prior randomized tPA trials until the IST3 randomized controlled trial of tPA up to 6 hours from symptom onset. Subgroup analysis suggested that patients with mild stroke did not appear to benefit from treatment, although a post hoc analysis restricted to treatment within 3 hours suggested a benefit, and the most recent meta-analysis of tPA studies, including IST3, suggests a potential benefit in mild stroke.…”
mentioning
confidence: 99%